Development of Human Facial Expression Game for Autism Children Using Design Thinking Method - Haq, Yaritza; Ashar, Muhammad; Kirana, Kartika Candra (Journal of Disruptive Learning Innovation (JODLI), 2022)
Facial expression is one of the important factors in interacting and communicating activities. People can know the emotions and feelings of the interlocutor through their facial expressions. However, this can be difficult while doing interactions with children with autism. These limitations become obstacles in socializing for children with autism because not everyone can understand their feelings. To overcome this problem, a study was proposed with the title "Development of a Game for Recognizing Human Facial Expressions for Children with Autism Using Design Thinking Methods". The existence of this research is expected to help children with autism to learn facial expressions according to the emotions they feel and can improve their social skills. The method used in this study is the Design Thinking method which consists of 5 stages, namely Empathize, Define, Ideate, Prototype, and Test.